Epidemiological profile of pertussis in Brazil from 2010 to 2019: a systematic review (Research, Society and Development, 2022)
Pertussis is a respiratory infection that severely affects humans, caused by bacteria of the genus Bordetella, especially the species B. pertussis and B. parapertussis, presenting an important cause of infant morbidity and mortality. This disease has received little attention from government authorities over the years, which can cause the disease to re-emerge in the future. This study aimed to carry out a systematic literature review on the epidemiology of pertussis in Brazil between the years 2010 to 2019. The study was carried out based on information collected in national (BVS, ANVISA, DATASUS) and international databases (PubMed, SciELO, CDC). When performing the statistical analysis of confirmed cases by region, there was a significant change in 2014 compared to other years in the Northeast region. While in the Southeast region, in 2013 there was a significant increase compared to 2012 and only reduced in 2015. In the South region, the increase in the number of cases occured sharply in 2012 and only decreased in 2017. In the Center-West region, 2014 was the only year that showes considerable statistical variety. Regarding the age group, children under 1 year old and between 10 and 14 years old are the ones with the highest number of pertussis cases. Regarding gender, no significant changes were detected. Health surveillance, compulsory notification of cases added to social participation are essential, so this disease can be eradicated from Brazil and the world.